Development of PAI Teaching Materials with an Interdisciplinary Approach - Tamuu, Safira Prakasa; Yahiji, Kasim; Ondeng, Syarifuddin; Arif, Muh. (Journal La Edusci, 2023)
This research uses Qualitative research. Qualitative Research is research that produces analytical procedures that do not use analytical procedures or other quantification methods. Qualitative Research is based on the effort of building their researched views that are detailed, formed with words, holistic and complicated images. Research results Teaching materials are prepared with the aim of providing teaching materials that are in accordance with the demands of the curriculum by considering the needs of students, namely teaching materials that are in accordance with the characteristics and settings or social environment of students. In addition, the development of teaching materials is expected to help students in obtaining alternative teaching materials in addition to textbooks that are sometimes difficult to obtain and facilitate teachers in carrying out their duties as an educator. Good teaching materials are teaching materials that really function optimally in the learning process so that the objectives of the learning itself can be achieved, therefore teaching materials must be as simple as possible to be understood and understood by students instead of making students more confused with existing teaching materials because teachers are less skilled in packaging them.